OPTIMIZATION OF SPRAY DRYING ON MICROENCAPSULATION GREEN COFFEE EXTRACT WITH RESPONSE SURFACE METHOD - Curie Hadyanti, Lucyana
Indonesia is an agricultural country, with a tropical climate with abundant coffee production, this is proven by Indonesia's coffee production in 2022 reaching 794.8 thousand tons and being ranked third in the world as the highest coffee producer. In coffee there are compounds that are beneficial for the body, namely phenolic compounds, caffeine, and antioxidants which can neutralize free radicals entering the body. The content of these compounds in green coffee is higher than in roasted coffee so that green coffee can be utilized optimally by extracting the polyphenolic compounds. However, the polyphenolic compounds in green coffee extract are sensitive to oxidation, so microencapsulation needs to be carried out. Drying microencapsulation of green coffee extract was carried out using the spray drying method which can coat the bioactive ingredients of green coffee extract with a higher yield than the freeze dry method. This research aims to determine the type of encapsulant material (maltodextrin, gum arabic, whey protein concentrate, and whey protein isolate) that is effective in the microencapsulation process by producing high levels of chlorogenic acid and phenolic compounds and low levels of moisture content; determine the effect of encapsulant material concentration and spray dryer inlet temperature on the quality of green coffee extract; determine the concentration of encapsulant materials and optimum inlet temperature in spray dryers. The quality of the green coffee extract tested included moisture content, chlorogenic acid content, total phenolic compounds, encapsulation efficiency. The optimization method used is the Response Surface Method (RSM) Central Composite Design (CCD) using Minitab and there are two variation factors, namely the concentration of the encapsulant material and the spray dryer inlet temperature. The best of encapsulant is whey protein isolate within phenol and chlorogenic loss during five days in storage respectively 4.01% and 5.29%. Spray dryer temperature significantly influence to chlorogenic acid and moisture content. Furthermore, WPI concentration significantly influence to chlorogenic acid and phenolic content. Optimum WPI concentration and spray dryer temperature respectively 17.07% and 174.4 oC.